3D electric field analysis of needleless electrospinning from a ring coil. (November 2014) - Wang, Xin; Wang, Xungai; Lin, Tong
Concentrated electric field is crucial in generation of needleless electrospinning, the electric field profile together with electric field strength of the spinneret affect the needleless electrospinning performance directly. Understanding the electric field of spinneret would definitely benefit the designing and optimization of needleless electrospinning. Based on the software COMSOL Multiphysics 3.5a, 3D finite element analysis has been used to analyze the electric field profile and electric field strength of a ring spinneret for needleless electrospinning. The electric field profile shows that strong electric field concentrates on the top of the ring with intensity higher than 70 kV/cm. The electric field of ring spinneret is greatly affected by the geometry of the ring and other experimental parameters such as applied voltage and collecting distance. The electric field analysis introduced in this study will be helpful in selecting proper spinneret and scaling up the production rate of nanofibers in needleless electrospinning.